Azúcar agridulce : trabajo y sindicatos en la agroindustria azucarera colombiana, 1960-1980 (2012)
ABSTRACT: This investigation reconstruct the employment context of the workers in the sugar industry in Colombia between 1960 and 1980, a period of profound changes in conditions of sugar workers on account of the transformations in this particular kind of industry. Between these transformations must be mentioned facts as the introduction of new technologies in the cane farming and the increase of need of farm workers, due to the expansion of cane farms and the rise of sugar production, because of the openness of markets such as United States, closed to cuban sugar because of the Revolution. On the other hand, the sugar labor union movement was immersed in contradictions that were problematic the unity between different organizations. In short, the mentioned circumstances substantially modified the labor outlook of sugar workers.